Cooperation with Strangers: Spillover of Community Norms - Molina, Mario; Nee, Victor; Holm, Hakan (Organization Science, 2023)
Why do leaders of organizations cooperate with players with whom they may never transact again? Such transactions can involve the incentives to exploit the other party because these interactions are not recurrent or embedded in networks. Yet, in a market economy, organizational actors learn to cooperate with strangers; otherwise, they risk closure from new ideas and business opportunities outside of their local community. With a large random sample of CEOs of manufacturing firms in the Yangzi River Delta region of China, we measured social norms using vignettes that describe hypothetical situations illustrating the social mechanisms of norm enforcement in respondents’ local communities. Several years later, in a laboratory-in-the-field experiment, we asked the same participants to play a one-shot Prisoner’s Dilemma (PD) game with a complete stranger. Our findings suggest that belief in the reliability of robust norm enforcement is positively associated with a higher probability of cooperation with strangers. To our knowledge, this mixed-method study is the first to explore the relationship between social norms and cooperation with strangers using a large sample of leaders of organizations outside the environment of the laboratory. Finally, to explore the generalizability of our behavioral findings, we experimentally manipulated norm vignettes and study the PD game in online experiments with managers in the Yangzi River Delta region. History: This paper has been accepted for the Organization Science Special Issue on Experiments in Organizational Theory. Funding: V. Nee gratefully acknowledges funding for research from the John Templeton Foundation (2005-2009 and 2015-2018), and from the College of Arts and Sciences at Cornell University. H. Holm thanks the Jan Wallander’s and Tom Hedelius’ Foundation for funding lab-in-the-field behavioral game. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2021.1521 .